Effect of Ageing on Oxidative Stress and Ascorbate-Glutathione Cycle in various RILs of Soybean - SANGITA YADAV; A TALUKDAR; SAMTA GUPTA; SUBHASH CHANDRA; K GAIKWAD; SK. LAL; SHIV K YADAV (Seed Research, 2026)
Effect of ageing on the antioxidant system was studied in three years old ambient-stored seeds of cultivated soybean variety DS 9712 (G.max.), wild type genotype DC 008-1(Gsoja) and 3 recombinant inbred lines (RILs) developed from inter-crossing of DS 9712 and DC 008-1. Germination in the seeds of DS 9712 was 13% as against 85% and above in the seeds of DC 008-1 and the 3 RILs. The concentration of the membrane- damageing substances like thiobarbituric acid reactive substances (TBARS) and conjugated dienes (CD) in the seeds of DS 9712, DC 008-1 and the recombinant inbred lines (RILs) was high, low and intermediate, respectively, which corresponded inversely with their level of germination. Among the RILS, RIL-2 (2_6_2) had the least concentration of TBRAS and CDs and the highest level of germination. TBRAS equivalent was found to be negatively correlated with the germination percent (r=-0.9966). The antioxidant enzymes involved in ascorbate- glutathione (ASA-GSH) cycle viz.; ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR). monodehydroascorbate reductase (MDHAR), and glutathione reductase (GR) were significantly low in DS 9712, while their concentration was medium to high among the RILs and DC008-1. The AsA-GSH system possessed weaker reduced: oxidized forms in DS 9712 as compared to DC 008-1 and the RILs. Efficient AsA-GSH cycle in the seeds of DC 008-1 and the 3 RILs might have prevented accumulation of reactive oxygen species (ROS) saving the membrane from damage leading to increased germination.